2022
DOI: 10.3390/biomedicines10050971
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Response to Immunotherapy Score: A Useful Tool for Identifying Eligible Patients for Allergen Immunotherapy

Abstract: A specific predictive tool of allergen immunotherapy (AIT) outcome has not been identified yet. This study aims to evaluate the efficacy of a disease score referred to as Predictive Response to Immunotherapy Score (PRIS) to predict the response to AIT and identify eligible patients. A total of 110 patients diagnosed with allergic rhinitis with or without concomitant asthma were enrolled in this study. Before beginning sublingual immunotherapy (SLIT), patients were evaluated by analyzing clinical and laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In patients with seasonal allergy, the oscillation of blood eosinophils in season and out of season is well known [45,46]. In some geographical regions, including Southern Italy, seasonal allergens can present very long-lasting periods of pollination and be the major allergens responsible for BA and AR [27,47,48]. Indeed, we previously reported that Parietaria and/or Gramineae grass were the dominant allergens in 75.5% of patients from Southern Italy affected by AR and/or BA, as assessed with a multi-parameter score [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with seasonal allergy, the oscillation of blood eosinophils in season and out of season is well known [45,46]. In some geographical regions, including Southern Italy, seasonal allergens can present very long-lasting periods of pollination and be the major allergens responsible for BA and AR [27,47,48]. Indeed, we previously reported that Parietaria and/or Gramineae grass were the dominant allergens in 75.5% of patients from Southern Italy affected by AR and/or BA, as assessed with a multi-parameter score [27].…”
Section: Discussionmentioning
confidence: 99%
“…In some geographical regions, including Southern Italy, seasonal allergens can present very long-lasting periods of pollination and be the major allergens responsible for BA and AR [27,47,48]. Indeed, we previously reported that Parietaria and/or Gramineae grass were the dominant allergens in 75.5% of patients from Southern Italy affected by AR and/or BA, as assessed with a multi-parameter score [27]. In our view, a single determination of AEC in these patients provides only a partial characterization of the eosinophilic status [26,49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the adult population, hazelnuts, peaches, apples, carrots, walnuts, melons, shellfish, sunflower seeds, and bananas are the foods most frequently associated with FA [ 20 ]. A reasonable explanation for this heterogeneity is found in pollen sensitization and cross-reactivity [ 7 , 87 , 90 ]. In fact, while FA in children occurs more frequently through primary sensitization (class 1 FA), in adults it occurs more frequently through cross-reactivity (class 2 FA) [ 20 , 23 , 91 ].…”
Section: Allergic Sensitization Profile In Different Geographical Areasmentioning
confidence: 99%
“…In recent years, a wide range of mAbs targeting IgE or type 2 cytokines have been proved to be highly effective and safe in reducing symptoms and exacerbation in patients with severe allergic and eosinophilic asthma [ 156 ]. However, these therapies are not suitable for about half of patients with severe asthma who often present with non-allergic, non-eosinophilic type 2-low asthma [ 60 , 157 , 158 ]. For this reason, in the era of precision medicine, investigating the different pathways involved in the different endotypes of asthma can help identify new targeted therapies ( Table 2 ).…”
Section: Target Therapies In Eosinophilic Airway Diseasementioning
confidence: 99%